PENGARUH HUMAN RESOURCES MANAGEMENT PRACTICE TERHADAP EMPLOYEE INTENTION TO STAY PADA PT MEDIA NUSANTARA INFORMASI (SINDO) - Yohana Fransiska Siahaan (Fakultas Ekonomi dan Bisnis Universitas Katolik Indonesia Atma Jaya, 2014)
This study aims to determine whether there isa significant effect of human resources management practices on employee intention to stay at PT Media Nusantara Informasi (Sindo). The analyses used multiple linear regressions with the sample of 100 full-time employees of PT Media Nusantara Infomasi (Sindo).As independent variables are Training and Development, Career Development, Compensation and Benefit, and Performance Appraisal, while Employees Intention to stay as dependent variable. The results showed that Training and Development, Career Development, Compensation and Benefit, and Perfomance Appraisal have positive significant effects on employee intention to stay. Further more, the results indicate that Compensation and Benefit dimension have a strongest effect.